CONCISE ROUTLEDGE ENCYCLOPAEDIA OF NEW CONCEPTS FOR INTERCULTURALITY - Dervin, Fred, 1974-; R'boul, Hamza; Chen, Ning (New perspectives on teaching interculturality., 2025)
This groundbreaking encyclopaedia presents 74 innovative concepts selected and elaborated by multilingual scholars, enriching critical discussions of the notion of interculturality in global scholarship. Many scholars are currently attempting to un-re-think and decolonize interculturality in different fields of research. Although ideas are critiqued and revised, this is happening in very similar linguistic terms as before. These potential attempts to decentre and decolonize could then be put into question. This book argues that knowledge production and negotiation should be exercised through alternative linguistic strategies, not for the sake of sounding different, but to advance new ways of defining, knowing and problematizing. The need to develop concepts in English and other languages is thus promoted in this encyclopaedia. Students, scholars and teachers with a sound background in intercultural studies will benefit most from the book. It will also appeal to anyone wishing to explore new ways of thinking, researching, speaking and writing about interculturality.